550‐Year Climate Periodicity in the Yunnan‐Guizhou Plateau During the Late Mid‐Holocene: Insights and Implications - Youwei Li; Dominik Fleitmann; Xiangli Wang; Carlos Pérez‐Mejías; Lijuan Sha; Xiyu Dong; Deyuan Wang; Rui Zhang; Xiaoli Qu; Hai Cheng (Geophysical Research Letters, 2023)
Abstract Significant multi‐centennial climate oscillations have been documented in a number of well‐dated climate records across the Holocene epoch and left various imprints in human cultural history. In this study, we developed speleothem δ13C, δ18O, trace elements, and lamina thickness records from the Yunnan‐Guizhou Plateau (YGP). Our high‐resolution and precisely dated records show a significant ∼550‐yr cycle as the dominant pattern of regional temperature and vegetation variations between ∼5,870 and ∼3,670 years ago. The phase analyses of the 550‐yr cycles among our speleothem records, other Northern Hemisphere climate records, solar activity index, and Atlantic meridional overturning circulation (AMOC) variations suggest that this climate cycle has a large spatial extent, and may be causally linked to the AMOC changes through coupled oceanic‐atmospheric processes. Additionally, the first cold phase of the ∼550‐yr cycle in our records coincides with the major cultural development on the YGP at ∼5,500–5,000 years ago, suggesting a critical relationship between climate and prehistorical cultural changes in the region.